Papua New Guinea: A Potential Refuge for Threatened Indo–Pacific River Sharks and Sawfishes - Grant, Michael I.; White, William T.; Amepou, Yolarnie; Appleyard, Sharon A.; Baje, Leontine; Devloo-Delva, Floriaan; Feutry, Pierre; Ibana, Dotty; Jogo, Dick J.; Jogo, Stanley; Kyne, Peter M.; Mana, Ralph; et al. (Frontiers in Conservation Science, 2021)
The conservation of threatened elasmobranchs in tropical regions is challenging due to high local reliance on aquatic and marine resources. Due primarily to fishing pressure, river sharks (Glyphis) and sawfish (Pristidae) have experienced large population declines in the Indo–Pacific. Papua New Guinea (PNG) may offer a refuge for these species, as human population density is low, and river shark and sawfish populations are thought to persist. However, few data are available on these species in PNG, and risk posed by small-scale fishers is poorly understood. This study observed small-scale fisheries in riverine and coastal environments of the East Sepik (northern region), Gulf, and Western Provinces (southern region) of PNG, and recorded elasmobranch catches during 2017–2020. We observed a total of 783 elasmobranchs encompassing 38 species from ten families. River sharks made up 29.4% of observations in the southern region, while sawfish made up 14.8% and 20.3% in the northern and southern regions, respectively. River sharks were commonly caught by small-scale fishers in lower riverine environments in southern PNG, while sawfish are generally less common and were mainly observed through dried rostra. The primary threat to river shark and sawfish populations is their capture by small-scale fishers targeting teleost's for swim bladder. Persisting populations of river sharks and sawfish indicate that PNG is the second known nation with viable populations in the Indo–Pacific. However, populations are declining or at high risk of decline, and fisheries management and conservation are required to secure PNG as a long-term refuge.